2017
DOI: 10.3390/biology6020022
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild Predation Dynamics in a Lake Ecosystem Based on a Coupled Hydrodynamic-Ecological Model: The Example of Lake Kinneret (Israel)

Abstract: The food web of Lake Kinneret contains intraguild predation (IGP). Predatory invertebrates and planktivorous fish both feed on herbivorous zooplankton, while the planktivorous fish also feed on the predatory invertebrates. In this study, a complex mechanistic hydrodynamic-ecological model, coupled to a bioenergetics-based fish population model (DYCD-FISH), was employed with the aim of revealing IGP dynamics. The results indicate that the predation pressure of predatory zooplankton on herbivorous zooplankton va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 66 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…The top-down and bottom-up effects on plankton-fish dynamics were discussed by Pal and Chatterjee [47,48], who confirmed that fish predation determines the abundance of herbivorous zooplankton, which, in turn, regulates phytoplankton biomass. However, it is also dependent on the growing season, especially due to the widely varied predatory zooplankton pressure on herbivorous zooplankton [49]. Thus, any changes in the abundance of planktivorous fish can directly affect both phytoplankton and zooplankton, but the role of omnivorous or predatory fish is also known.…”
Section: Discussionmentioning
confidence: 99%
“…The top-down and bottom-up effects on plankton-fish dynamics were discussed by Pal and Chatterjee [47,48], who confirmed that fish predation determines the abundance of herbivorous zooplankton, which, in turn, regulates phytoplankton biomass. However, it is also dependent on the growing season, especially due to the widely varied predatory zooplankton pressure on herbivorous zooplankton [49]. Thus, any changes in the abundance of planktivorous fish can directly affect both phytoplankton and zooplankton, but the role of omnivorous or predatory fish is also known.…”
Section: Discussionmentioning
confidence: 99%
“…Zooplankton is under two directive eco-forces: A) Cascading top-down pressure by zooplanktivore fishes, but invertebrate predation is negligible, and increase in the Bleak population in the lake was documented [22][23][24][25]; B) Bottom-up through nutrients controlling the available algal density and likely the zooplankton is significantly affected by temperature and temperature elevation due to climate change (Figure 14) [4,5] also supported the forceful impact on metabolic activity. This paper has focused on the relation between climate change and Zooplankton ecology.…”
Section: Synopsis: Future Perspective Of Zooplankton Research In Lake Kinneretmentioning
confidence: 99%
“…Intraguild predation (IGP) is a complex interspecific relationship prevalent in ecosystems, where two predators of the same trophic level compete for prey resources and may also act as predators of each other [ 1 ]. Intraguild predation is prevalent in various ecosystems [ 2 , 3 ]; for example, some small fish and shrimp in lake ecosystems are in competition for food resources such as zooplankton and also have predatory relationships [ 4 ].…”
Section: Introductionmentioning
confidence: 99%